ChemInform Abstract: Electrolysis of Ionic Liquids: A Possible Keystone for the Achievement of Green Solvent—Catalyst Systems. Issue 28 (21st June 2013) - Feroci, Marta; Chiarotto, Isabella; Inesi, Achille
Abstract Review: 187 refs.